Analisis Kepuasan Penumpang Dalam Menggunakan Jasa Transportasi PO. Sari Kencana - -, Ermina - (Jurnal Mahasiswa Prodi Manajemen Fakultas Ekonomi, 2016)
This study aimed to analyze the Passenger Satisfaction In Using PO Transport This study aimed to analyze the Passenger Satisfaction In Using PO Transport Services. The population in this study is that consumers never use PO Transport Services. Kencana Sari and used a sample of 87 consumers. Sampling research was done by calculating the formula Slovin and respondents were selected at random. Technical analysis of the data used is descriptive analysis is to describe a glimpse of the results of survey respondents, the average value (mean) of each item and the total items and questions used to determine achievement of the respondents to the spread of the respondents' answers. Results of the study by counting the TCR showed that indicators of physical evidence (tangible) had a total value of 77.6 TCR categorized quite satisfied. Indicators of empathy (empathy) have a total value of 83.3 TCR categorized satisfied. Indicators of reliability (reliability) have a total value of 77.13 TCR quite satisfied. Indicator responsiveness (responsiveness) had a total value of 79.8 TCR categorized quite satisfied. And indicators assurance (assurance) have a total value of TCR 78 categorized quite satisfied. Â